Near Critical and Supercritical Impregnation and Kinetic Release of Thymol in Lldpe Films Used for Food Packaging - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A (2014)
Sin Editorial Disponible